The genus Neoseiulus Hughes (Mesostigmata: Phytoseiidae) in the Espinhaço Range, a great reservoir of biodiversity in Brazil - Ferragut, Francisco; Navia, Denise (Zootaxa, 2022)
Several surveys were conducted between 2010 and 2012 in the Brazilian range Serra do Espinhaço, a highly biodiverse region extending more than 1000 km in the states of Bahia and Minas Gerais. We report in this paper eight species of the genus Neoseiulus Hughes collected on natural, non-cultivated, vegetation. Two of these species are described, illustrated and proposed as new taxa, N. cipoensis sp. nov. and N. diamantinus sp. nov. New morphological information as well as host-plants and geographical distribution are provided for six additional species, N. benjamini (Schicha), N. californicus (McGregor), N. goiano Demite, Cavalcante & Lofego, N. idaeus Denmark & Muma, N. melinis Lofego & Moraes, and N. tunus (De Leon).